Making regions: localisation and the new periphery in emerging regional governance. Issue 2 (3rd April 2020) - Choice, Gary; Butt, Andrew
ABSTRACT: Goals of collaborative metropolitan and regional governance are critical issues for development and intergovernmental relations in contemporary Australia. Experiments in local government restructure, new models of direct Commonwealth-local funding and the formation of regional networks of local government each respond to governance reform and fiscal challenges. Such approaches offer new opportunities for co-ordinated projects, funding innovation and efficiencies in service delivery, and the conception and construction of the institutions of regional governance offer opportunities for addressing the fragmentary capacity of local government in Australia. Yet they also reveal and enforce new peripheralisation and marginalisation of local place and difference. In the wake of recent local council amalgamations and the concurrent re-conceptualising of operational regions in NSW, this paper explores how local actors (specifically local government planners) understand and react to the notions of regionality in their day-to-day and strategic work, and how these ideals are created and imposed, given historic geographies of socio-economy and governance. Through interviews with local planners, it will explore the local governance realities of newly conceived regionality in the Hunter and North Coast regions, and consider this in the context of an emerging policy discourse of regions and megaregions in non-metropolitan New South Wales.